2009
DOI: 10.1038/jhh.2009.90
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of initiating treatment with valsartan/hydrochlorothiazide in patients with stage-1 or stage-2 hypertension

Abstract: This prospective, 6-week, multicenter, double-blind study examined the benefits of initiating treatment with combination valsartan/hydrochlorothiazide (HCTZ) compared with initial valsartan monotherapy for 648 patients with stage-1 or stage-2 hypertension (age=52.6±10 years; 54% male; baseline blood pressure (BP)=161/98 mm Hg, 32% stage 1). Patients were randomized to valsartan 80 mg (V-low), valsartan 160 mg (V-high) or valsartan/HCTZ 160/12.5 mg (V/HCTZ), and electively titrated after weeks 2 and 4 to the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Though the number of discontinuations leading to study drug related AEs were higher in the valsartan group, they were mild to moderate in nature, and the only event that occurred in more than one patient was nausea. In addition, a previously conducted study in 6-16 year old patients found valsartan to be well tolerated [24] and it has also been shown to have a good tolerability profile in a number of different adult patient populations across a multitude of clinical studies [18][19][20]33]. …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Though the number of discontinuations leading to study drug related AEs were higher in the valsartan group, they were mild to moderate in nature, and the only event that occurred in more than one patient was nausea. In addition, a previously conducted study in 6-16 year old patients found valsartan to be well tolerated [24] and it has also been shown to have a good tolerability profile in a number of different adult patient populations across a multitude of clinical studies [18][19][20]33]. …”
Section: Discussionmentioning
confidence: 98%
“…Valsartan, a well known ARB, has proven efficacy and safety when used either as monotherapy or in combination to treat hypertension in adults [18][19][20]. A doseresponse study in children aged 6-16 years demonstrated that valsartan was efficacious and well tolerated in doses ranging from 10 to 160 mg [21].…”
Section: Introductionmentioning
confidence: 98%
“…Valsartan is an ARB that has proven efficacy and safety when used either as monotherapy or in combination to treat hypertension in adults [14][15][16][17]. This ARB has also demonstrated efficacy and safety in doses ranging from 10 to 160 mg in children aged 6-16 years [18].…”
Section: Introductionmentioning
confidence: 98%
“…Hypertension is one of the most prevalent chronic adult illnesses today and cannot be cured, but it can be controlled [1]. The pharmacological treatment for control of hypertension utilizes various drug therapies, single doses or associations of diuretics, beta-blockers, calcium channel blockers, angiotensin converting enzyme (ACE) inhibitors and angiotensin II receptor (AT1) antagonist (ARA) [2][3][4][5]. Valsartan (VAL, Figure 1) is one of the angiotensin II receptor (AT1) antagonists recommended for treatment of hypertension, postmyocardial infarction or congestive heart failure and chemically it is N-(1-oxopentyl)-N-[[2′-(1H-tetrazol-5yl)[1,1′-biphenyl]-4-yl]methyl]-L-valine1.…”
Section: Introductionmentioning
confidence: 99%